IN VITRO ANTIOXIDANT ACTIVITY STUDIES OF AQUEOUS- AND FREEZE-DRIED FRUIT EXTRACT OF RHUS CHINENSIS AND JUICE OF CITRUS MACROPTERA, THEIR COMPARATIVE STUDIES - SANGTAM, SETINGLA; K, THANZAMI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objective of the study is to evaluate in vitro antioxidant activity of aqueous- and freeze-dried fruits extracts of Rhus chinensis and Citrus macroptera and their comparative studies. Methods: The sumac fruit extracts were prepared by macerating in distilled water for 36 h, strained, and concentrated. Hatkora juice was used as it is for further concentration. Both the sample were dried using two methods, that is, evaporation in the water bath at 50°C and freeze-dried in a lyophilizer. The total phenolic content and total flavonoid content were determined using Folin–Ciocalteu and aluminum chloride method. The extracts were evaluated for antioxidant activity by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay and reducing power assay. Results: Both sumac extract and Hatkora juice show potent antioxidant activity. When compared, the freeze-dried sample shows better activity as compared to the aqueous dried sample in both DPPH and reducing power assay. Conclusions: This study result shows high phenolic and flavonoid content which is responsible for its high antioxidant activity. This suggests that the fruits can be viewed as a potential source of natural antioxidants that can provide valuable functional ingredients useful for the prevention of diseases related to oxidative stress, dietary supplements, functional food, nutraceuticals, etc.